2010
DOI: 10.1007/s10152-010-0204-5
|View full text |Cite
|
Sign up to set email alerts
|

External morphology of the cycliophoran dwarf male: a comparative study of Symbion pandora and S. americanus

Abstract: Cycliophora is a recently described phylum to which only two species have been assigned so far, Symbion pandora and S. americanus. The cycliophoran life cycle is complex and alternates between asexual and sexual stages. Although not recognized as an entirely independent freeswimming stage when the phylum was first described, the dwarf male has a remarkably complex bodyplan albeit its very small size (approx. 30-40 lm in length). Aiming to increase the knowledge on the gross morphology of the cycliophoran dwarf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Among Spiralia (to which rotifers belong(40-42)) it has been reported in e.g. Cycliophora(43-47), Orthonectida(48), which are now considered parasitic annelids(49, 50), some octopi(51) and in several annelid clades including some dinophilids(52-54), Osedax (55-57), Spionidae(58, 59) and bonellid echiurans(60). There are two proposed mechanisms responsible for the origin of dwarfism: progenesis or reduction(61, 62), which are reflected in the morphology of the dwarfed forms, including their nervous system and musculature(52).…”
Section: Discussionmentioning
confidence: 99%
“…Among Spiralia (to which rotifers belong(40-42)) it has been reported in e.g. Cycliophora(43-47), Orthonectida(48), which are now considered parasitic annelids(49, 50), some octopi(51) and in several annelid clades including some dinophilids(52-54), Osedax (55-57), Spionidae(58, 59) and bonellid echiurans(60). There are two proposed mechanisms responsible for the origin of dwarfism: progenesis or reduction(61, 62), which are reflected in the morphology of the dwarfed forms, including their nervous system and musculature(52).…”
Section: Discussionmentioning
confidence: 99%
“…5.2A ), encysts, and generates internally one to three mature dwarf males with a cuticular penile structure ( Fig. 5.2D ; Neves et al 2010c ). Electron microscopy studies showed that younger males are larger and possess more nucleated somatic cells (aproximately 200) than mature individuals, who only have around 50 nucleated cells and nuclei-free muscles and epidermis (Neves and Reichert 2015 ).…”
Section: Life Cycle Stages and Developmentmentioning
confidence: 94%
“…The sexual part of the life cycle involves initially a Prometheus larva and a female, which are also generated by inner budding inside the feeding stage. Once freed, the Prometheus larva settles on the trunk of a feeding individual and generates dwarf males inside its body (Obst and Funch 2003;Neves et al 2010). The female is impregnated by the dwarf male and the embryo develops into a chordoid larva (Funch 1996;Neves et al 2012).…”
Section: Introductionmentioning
confidence: 99%